Detection and intervention strategies by primary health care professionals in suspected elder abuse - Ferreira, Mafalda; Santos, César Lares dos; Vieira, Duarte Nuno (Ordem dos Médicos, 2015)
Introduction: Primary health care professionals are in a privileged position to recognize and manage cases of suspected elder abuse. The purpose of this study was to provide some insight of these professionals’ views and knowledge on this subject. Material and Methods: A questionnaire was elaborated and sent to physicians and nursing staff practicing in 12 different health care units in Coimbra. The data collected included parameters related to demography, perception of abuse and management strategies, personal experience and training on this subject. Results: The global response rate was 67.9% corresponding to 127 validated questionnaires. From the results found, we highlight the following: there was a significant contact between these professionals and older people; most (64.6%) considered the abuse as more prevalent in the familiar context and 32.3% signed negligence as the most common type; the majority of professionals considered themselves as useful (97.6%); the uncertainty in the diagnosis was one of the most important causes for non-reporting; there were doubts concerning mandatory report of abuse to judicial authorities. It was also found that 87.4% of the respondents stated they would feel more comfortable having formal protocol to handle these cases and this subject was not included in the training curriculum of 70.9% of the respondents. Discussion: The significant contact between older population and health care professionals allows for an early diagnose and intervention. The professionals showed knowledge in accordance to some studies, namely, as to the context and prevalence of abuse. Doubts as to the best way to manage these cases could be solved by implementing protocols and by specific training, which is a fundamental cornerstone for preparing professionals to deal with these kind of cases. Conclusion: Health care professionals seemed to be aware of the relevance of elder abuse, as well as the importance of their role in preventing and diagnosing these abuses. However, a more extensive approach on this subject during clinical training and the definition of general clinical guidelines are important to increase the professionals’ confidence in managing suspected cases.
Keywords: Elder Abuse; Mistreatment; Primary Health Care; Portugal